Optimal scheduling of water network repair crews considering multiple objectives - Osman, Hesham; Ammar, Marwan; El-Said, Moheeb (Journal of Civil Engineering and Management, 2017)
Water main breaks disrupt water services and impact traffic flow along congested city roads. Dispatching water pipe repair crews needs to consider several factors that include: 1) the priority of repair site; 2) the suitability and efficiency of the construction crew in repairing a particular break type; and 3) the time required for crews to travel between break sites. This paper presents a simulation-based multi-objective optimization model to schedule repair crews across water network break sites in an urban setting. Discrete-event simulation models for the water pipe repair process are developed to account for various repair methods. These models are subsequently integrated within a GA-based multi-objective optimization model that considers the following objectives: 1) minimizing the total repair time required to complete all breaks; 2) minimizing the total cost to complete the breaks; and 3) minimizing the cumulative impact of all breaks incident on road users and water customers. A case study for the water network on the City of Damietta, Egypt is used to demonstrate the capabilities of the model. Results show a 21% reduction in repair time and 50% reduction in user impact compared to heuristic crew allocation methods used by the water utility.